Innovative Approaches to Stress Reduction: A Review of Virtual Reality Therapy in University-Going Students: Stress Reduction Approaches - zahidullah, .; Bashir, Shahzad; Kumar, Santosh (Pakistan Journal of Health Sciences, 2024)
Students face unique challenges in terms of stress and Virtual Reality Technology (VRT) is emerging as a novel method for managing it. It has immersive and engaging nature that makes it potentially more effective stress management tool. Objective: To analyzed the effectiveness of VRT in managing stress among university students. It also evaluates student willingness to adopt these interventions compared to traditional methods. Methods: Narrative approach was used to review existing literature, focusing on studies that assessed the impact of VRT on student stress levels. Data were analyzed considering variations in VR content, delivery format, and participant demographics. Results: The review revealed that students generally show a willingness to use VRT for stress management but the effectiveness of these interventions was inconsistent. VRT using natural environments especially with greenery was more effective in reducing stress as compared to virtual settings. However, some studies reported no significant difference between VRT and traditional methods. Conclusions: VRT has potential in enhancing student well-being but its effectiveness was influenced by the type of VR content, delivery method, and individual characteristics. The limitations suggest that VRT was not a definitive solution to stress. This shows that further research was needed to optimize VRT interventions and to implement them to broader academic settings.